Back Cover: Supramolecular Fullerene Polymers and Networks Directed by Molecular Recognition between Calix[5]arene and C60 (Chem. Eur. J. 49/2014). Issue 49 (1st December 2014) - Hirao, Takehiro; Tosaka, Masatoshi; Yamago, Shigeru; Haino, Takeharu
<x xml:space="preserve">Abstract</x> New linear and networked fullerene polymeric organizations were synthesized through self‐assembly directed by molecular recognition of a biscalix[5]arene and C60. The cover represents the schematic representation of the supramolecular organization processes for the formation of the linear and network fullerene polymers. For more details see the Full Paper by T. Haino et al. on page 16138 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>